Ag-ZnO Incorporated Silica Based Bio-Nanocomposite Prepared by Low Cost Method for Photocatalytic Dye Degradation. Issue 5 (3rd May 2016) - Hong, Tan Chuan; Radhika, T.; Ramalingam, R. Jothi; Adam, Farook
Abstract : Zinc-silver incorporated rice husk silica catalysts were prepared by a simple sol-gel precipitation. The FT-IR and thermal analyses are confirms the complete removal of the template after calcination at 773 K. From the XRD pattern, it could observed that zinc and silver which incorporated into rice husk silica with its characteristic crystalline form. Methylene blue (MB) was used to evaluate the photocatalytic activity of the prepared samples. During photodegradation, concentration of methylene blue was decreased within 1 h under the studied reaction condition. The incorporation of silver ions on rice husk silica improves the crystalinity and activity.